Characteristics of cystic fibrosis‐related diabetes: Data from two different sources the European cystic fibrosis society patient registry and German/Austrian diabetes prospective follow‐up registry. Issue 3 (7th March 2019) - Prinz, Nicole; Zolin, Anna; Konrad, Katja; Nährlich, Lutz; Laubner, Katharina; Olesen, Hanne V.; Bauer, Maria; Jung, Andreas; Frischer, Thomas; Holl, Reinhard W.; ,
Abstract : Background: Standardized patient registries provide a unique basis to get insight into cystic fibrosis (CF)‐related diabetes (CFRD), the most common comorbidity in CF. Methods: A total of 3853 CFRD patients from the European CF Society Patient Registry (ECFSPR) and 752 from the German/Austrian diabetes prospective follow‐up (diabetes patienten verlaufsdokumentation [DPV]) were studied. To adjust for age and sex, multivariable regression was used (SAS 9.4). Results: DPV subjects were younger (26.5 [20.2‐32.6] vs 28.3 [21.7‐36.0] years, P < 0.001) and more often female (59.6 vs 50.9%, P < 0.001). In both registries, F508del homozygotes were most frequent, with higher proportion in DPV (80.9 vs 57.8%, P = 0.003). After adjustment, lung‐transplantation (LTX) was more common in ECFSPR (18.9 vs 4.9%, P < 0.001), although duration since LTX (4.8 ± 0.2 vs 5.5 ± 0.7 years, P = 0.33) did not differ. In DPV patients without LTX, a lower BMI (19.6 ± 0.1 vs 21.0 ± 0.1 kg/m 2, P < 0.001), higher proportion of underweight (41.2 vs 20.2%, P < 0.001) and a tendency towards worse lung function (%FEV1 : 42.3 ± 4.2 vs 48.3 ± 0.5%, P = 0.16) were observed. Conclusions: Between both registries, demographic and clinical differences of CFRD were present. Besides different kind of data sources, diverse treatment structures between countries may play a role. The results may further indicate a more serious illness in patients treated in specialized diabetes clinics, documenting their data in DPV.